Respuesta :
Answer:
The solutions to the system of the equations by the elimination method will be:
[tex]x=2,\:z=-1,\:y=2[/tex]
Step-by-step explanation:
Given the system of the equations
[tex]2x\:+\:2y\:+z\:=\:7[/tex]
[tex]-x-\:y\:+z\:=\:-5[/tex]
[tex]x+3y-4z=12[/tex]
solving the system of the equations by the elimination method
[tex]\begin{bmatrix}2x+2y+z=7\\ -x-y+z=-5\\ x+3y-4z=12\end{bmatrix}[/tex]
[tex]\mathrm{Multiply\:}-x-y+z=-5\mathrm{\:by\:}2\:\mathrm{:}\:\quad \:-2x-2y+2z=-10[/tex]
[tex]\begin{bmatrix}2x+2y+z=7\\ -2x-2y+2z=-10\\ x+3y-4z=12\end{bmatrix}[/tex]
[tex]-2x-2y+2z=-10[/tex]
[tex]+[/tex]
[tex]\underline{2x+2y+z=7}[/tex]
[tex]3z=-3[/tex]
[tex]\begin{bmatrix}2x+2y+z=7\\ 3z=-3\\ x+3y-4z=12\end{bmatrix}[/tex]
[tex]2x+6y-8z=24[/tex]
[tex]-[/tex]
[tex]\underline{2x+2y+z=7}[/tex]
[tex]4y-9z=17[/tex]
[tex]\begin{bmatrix}2x+2y+z=7\\ 3z=-3\\ 4y-9z=17\end{bmatrix}[/tex]
Rearranging the equations
[tex]\begin{bmatrix}2x+2y+z=7\\ 4y-9z=17\\ 3z=-3\end{bmatrix}[/tex]
solve [tex]3z=-3[/tex] for z:
[tex]z=-1[/tex]
[tex]\mathrm{For\:}4y-9z=17\mathrm{\:plug\:in\:}z=-1[/tex]
solve [tex]4y-9\left(-1\right)=17[/tex] for y:
[tex]4y-9\left(-1\right)=17[/tex]
[tex]4y+9=17[/tex]
[tex]4y=8[/tex]
[tex]y=2[/tex]
[tex]\mathrm{For\:}2x+2y+z=7\mathrm{\:plug\:in\:}z=-1,\:y=2[/tex]
solve [tex]2x+2\cdot \:2-1=7[/tex] for x:
[tex]2x+2\cdot \:2-1=7[/tex]
[tex]2x+3=7[/tex]
[tex]2x=4[/tex]
[tex]x=2[/tex]
Therefore, the solutions to the system of the equations by the elimination method will be:
[tex]x=2,\:z=-1,\:y=2[/tex]